Introduction to Arabic Dictation (Imlā’): A Foundational Guide to Writing Accuracy - Wira Nama Wira Bangsa; Ahmad Azkia Salam; Nur Aunie Batrisya (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The mastery of imlāʾ (Arabic dictation) constitutes a fundamental component of Arabic language learning, yet it often receives less pedagogical attention compared to reading, speaking, and grammar. This study investigates the implementation of Kitāb Imlāʾ by Ustaz Hasan Basri as a practical instructional resource designed to improve students’ spelling accuracy. Employing a qualitative case study at Pondok Pesantren Darullughah Wadda’wah in Pasuruan, Indonesia, the research involved 32 fourth-grade (ibtidāʾī) students through classroom observations, semi-structured interviews, and pre- and post-test dictation tasks. Findings indicate that the systematic use of the kitab, with its step-by-step exercises and repetitive drills, effectively reduced error rates from 38% to 17%. Students demonstrated significant improvement in distinguishing tāʾ marbūṭah from hāʾ and in applying hamzah rules, while teachers confirmed that the kitab provided practical exercises rather than abstract theory. Nonetheless, certain challenges persisted, particularly in mastering hamzah rules and overcoming mother-tongue interference. The study highlights the value of localized, practice-oriented resources in enhancing imlāʾ pedagogy and recommends integrating Kitāb Imlāʾ as a central element in Arabic literacy instruction.